KEBERLANJUTAN USAHATANI KOPI AGROFORESTRI DI KECAMATAN PULAU PANGGUNG KABUPATEN TANGGAMUS - Annisa Incamilla; Bustanul Arifin; Adia Nugraha (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2015)
This research purposes to analyze comparison on the level of certified and non-certified coffee farmer’s farm income, comparison on the level of certified and non-certified coffee farmer’s participation in farmer group activities and assuming acceptance of indirect benefits obtained by coffee farmers in the process of farming.  The study was conducted in Tekad and Tanjung Rejo Villages, Pulau Panggung Sub Districts of Tanggamus Regency.  Total respondents were 70 coffee farmers, consisting of 35 certified coffee farmers and 35 non-certified coffee farmers.  The samples were selected by simple random sampling method.  Research data were collected in September to November 2014 and analyzed by qualitative and quantitative analysis.  The research results showed that the certified coffee farmer's income was higher than the non-certified coffee farmers.  Similarly, the research result about level of participation in the activities of farmers showed certified coffee farmer’s level of participation in the activities of farmer group was higher than non-certified coffee farmers; in addition, assuming acceptance of indirect benefits that can be accepted by coffee farmers was Rp4,191,080.00 per hectare. Key words: certified coffee, comparison, sustainability